Disruption : the global economic shocks of the 1970s and the end of the Cold War - De Groot, Michael, 1988- (Ithaca [New York] : Cornell University Press, 2024)
"This book illuminates the link between the global economic shocks of the 1970s and the end of the Cold War"--
American power and the collapse of the Bretton Woods system -- Eastern European development and Soviet subsidies -- The West and the oil shock -- Twin oil crises behind the Iron Curtain -- The travails of Jimmy Carter -- The Soviet umbrella and the Volcker shock -- Managing the inversion -- The collapse of the Soviet welfare empire.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on February 28, 2024).
Added to collection customer.56279.3
Keywords: 1900-1999; World politics -- 1945-1989.; International economic relations -- History -- 20th century; Cold War -- Economic aspects; Cold War -- Influence; Politique mondiale -- 1945-1989.; Guerre froide -- Aspect économique; HISTORY / United States / 20th Century; International economic relations; War -- Economic aspects; War -- Influence; World politics; elektronické knihy; electronic books